KEANEKARAGAMAN KEPITING PADA EKOSISTEM MANGROVE DI PERAIRAN NATUNA, KEPULAUAN RIAU - Ernawati Widyastuti (Scripta Biologica, 2018)
ABSTRACTThis study aims to determine the diversity of crabs in the mangrove ecosystems in Natuna waters, Riau Islands. The study was conducted on 23 October to 5 November 2014. The crabs were collected from eight research stations using random method, by putting a transect quadrant of 1 x 1 m2 on an area of 10 x 10 m2 area at each mangrove observation station. Results obtained 274 individuals, from 21 species, 11 genera and 8 families. Crabs of the family Sesarmidae most diverse with 8 specie: Clistocoeloma sp., Nanosesarma edamensis, Parasesarma leptosoma, Parasesarma sp1., Perisesarma cf. brevicristatum, Perisesarma semperi, Perisesarma sp1. and Sarmatium crassum. Based on quantitative analysis, the index value of diversity ranged from 0.932 – 2.028, with the highest value obtained at Cemaga Utara (St. NTNM02). The eveness index  in the range of 0.579 - 0.881 with the highest eveness at Cemaga Selatan (St. NTNM01).